Composite structure sagger for lithium battery positive electrode material and preparation method of composite structure sagger
By adopting a composite structure design in the casing of the cathode material of lithium-ion battery and using the combination of carbon cladding and garnet, the problem of volume expansion and strong alkaline erosion of the casing during high-temperature solid-phase synthesis is solved, which is significantly Improves its corrosion resistance and thermal shock resistance and extends its service life.
Patent Information
- Application Number
- CN202411354780.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing lithium-ion battery cathode material is easily reacted with the material during the high-temperature solid phase synthesis, resulting in volume expansion and peeling, and faces strong alkaline erosion, resulting in short life and affecting battery performance.
Using a composite structure silhouette, a carbon cladding layer is formed by immersing mullite, cordierite and corundum in an aqueous solution of furfurfuranol and adding oxalic acid to polymerize at high temperature. A garnet is added to the outer and inner layer, and then calcined by pressing and molding. The composite structure of the lithium battery positive electrode material is used to improve corrosion resistance and thermal shock resistance.
It effectively improves the anti-erosion and thermal shock performance of the silo, extends the service life, and enhances the mechanical properties and thermal shock performance of the cathode material of lithium battery.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sagger kiln preparation, in particular to a composite structure sagger for lithium battery positive electrode material and a preparation method thereof. Background Art
[0002] With the rapid development of new energy vehicles, energy storage and other industries, lithium-ion batteries with advantages such as green high energy, long cycle life and high safety have been widely studied. They are mainly composed of positive electrode, negative electrode, electrolyte and separator. Among them, positive electrode material is the key core material of lithium-ion battery and accounts for the largest proportion of cost, so positive electrode material is crucial to the performance of lithium-ion battery.
[0003] According to the different positive electrode materials of lithium batteries, their preparation methods are also different. Due to the requirements of industrial production on process equipment and economy, high-temperature solid-phase synthesis is still widely used in many synthesis methods because of its simple preparation process, low production cost, high output and short production cycle. In the high-temperature solid-phase preparation process, the alkaline lithium source and the precursor are first mixed, and then placed in a sagger and calcined in a kiln. Sagger is an important carrier in the sintering process of positive electrode materials for lithium-ion batteries. At present, cordierite-mullite / spinel materials are mainly used, but the acidic oxides in its components, such as silicon dioxide, are easy to react with the alkaline components in the positive electrode materials to form lithium silicate, β-eucryptite, etc., and cause volume expansion, resulting in the peeling and damage of the sagger, and at the same time causing "lithium loss" of the positive electrode materials. It can be seen that the sagger is not only damaged by thermal stress during the reciprocating service process, but also faces strong alkaline erosion of the positive electrode materials of lithium-ion batteries. Therefore, further improving the service life of the sagger to achieve its corrosion resistance and longevity has positive significance for the development of lithium-ion batteries. Summary of the invention
[0004] The object of the present invention is to provide a composite structure sagger for lithium battery positive electrode material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A composite structure sagger for lithium battery positive electrode materials. The composite structure sagger for lithium battery positive electrode materials is prepared by firstly immersing mullite, cordierite and corundum in a furfuryl alcohol aqueous solution respectively, adding oxalic acid for polymerization and then calcining at high temperature to obtain carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum; mixing mullite, cordierite, corundum, leucite, yellow dextrin and water as the outer layer of the sagger, mixing carbon-coated mullite, carbon-coated cordierite, carbon-coated corundum, leucite, yellow dextrin and water as the inner layer of the sagger, and calcining the inner and outer layer structures after composite compression molding to obtain the composite structure sagger for lithium battery positive electrode materials.
[0007] Preferably, the outer layer of the sagger comprises the following components by mass: 25-30 parts of mullite, 35-45 parts of cordierite, 10-15 parts of corundum, and 8-10 parts of leucite.
[0008] Preferably, the inner layer of the sagger comprises the following components by mass: 25-30 parts of carbon-coated mullite, 35-45 parts of carbon-coated cordierite, 10-15 parts of carbon-coated corundum, and 8-10 parts of leucite.
[0009] Preferably, the contents of various particle size components of the mullite, cordierite, corundum, leucite, carbon-coated mullite, carbon-coated cordierite, and carbon-coated corundum are as follows: 3-5% for particles above 10 mesh; 20-25% for particles between 10 and 18 mesh; 15-20% for particles between 18 and 50 mesh; 20-25% for particles between 50 and 200 mesh; 20-25% for particles between 200 and 325 mesh; and 10-15% for particles below 325 mesh.
[0010] A method for preparing a composite structure sagger for lithium battery positive electrode material, comprising the following preparation steps:
[0011] (1) Carbon coating: Mullite, cordierite and corundum were soaked in a furfuryl alcohol aqueous solution by weight, stirred at 200-300 r / min for 30-40 min at a material-liquid ratio of 1 g / 10 ml at 80-90° C., and an equal volume of 0.3 mol / L oxalic acid aqueous solution was added dropwise at 3-4 drops per second at 80-90° C., stirred at 200-300 r / min for 6-8 h, filtered, washed with pure water 3-4 times, vacuum dried at 50-60° C. for 8-10 h, calcined at 800-900° C. for 2-3 h in an argon atmosphere, with a heating rate of 5° C. / min, and naturally cooled to room temperature to obtain carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum;
[0012] (2) Compression molding: weigh 25-30 parts of mullite, 35-45 parts of cordierite, 10-15 parts of corundum, 8-10 parts of leucite, then add 5-7 parts of yellow dextrin and 3-5 parts of water, mix evenly, age for 24 hours, put into a mold with a thickness of 12-15 mm, then weigh 6-7 parts of carbon-coated mullite, 9-11 parts of carbon-coated cordierite, 2.5-4 parts of carbon-coated corundum, 2-2.5 parts of leucite, 1-2 parts of yellow dextrin, 0.75-1.25 parts of water, mix evenly, age for 24 hours, put into a mold with a thickness of 3-4 mm, seal and cure at room temperature for 24 hours, press and mold at a pressure of 150 MPa, hold the pressure for 10-14 hours, and dry at room temperature and 110° C. for 24 hours to obtain a sagger green body;
[0013] (3) Calcination: The sagger green body is calcined at a sintering temperature and naturally cooled to room temperature to obtain a composite structure sagger for lithium battery positive electrode materials.
[0014] Preferably, the furfuryl alcohol aqueous solution in step (1) is prepared by uniformly mixing furfuryl alcohol and pure water in a volume ratio of 1:40.
[0015] Preferably, the sintering temperature in step (3) is: 0-100°C, heating rate 1.25°C / min; 100-900°C, heating rate 5°C / min, keeping at 900°C for 30min; 900-1200°C, heating rate 4°C / min; 1200-1400°C, heating rate 2.5°C / min, keeping at 1400°C for 3h.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0017] When preparing a composite structure sagger for lithium battery positive electrode materials, the present invention comprises the following steps: firstly, mullite, cordierite and corundum are immersed in a furfuryl alcohol aqueous solution respectively, oxalic acid is added for polymerization, and then the mixture is calcined at high temperature to obtain carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum; mullite, cordierite, corundum, leucite, yellow dextrin and water are mixed as an outer layer of the sagger, and carbon-coated mullite, carbon-coated cordierite, carbon-coated corundum, leucite, yellow dextrin and water are mixed as an inner layer of the sagger; and the inner and outer layer structures are compositely pressed and formed, and then calcined to obtain the composite structure sagger for lithium battery positive electrode materials.
[0018] Firstly, a layer of polyfurfuryl alcohol is in situ polymerized on the surface of mullite, cordierite and corundum by furfuryl alcohol under the catalysis of oxalic acid, and then calcined at high temperature to form a carbon layer to obtain carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum. The raw materials coated with the carbon layer have effective corrosion resistance, the carbon layer has good resistance to alkali metal corrosion, and white garnet also has good corrosion resistance. A part of the added white garnet can be dispersed near the carbon-coated raw materials to protect the carbon layer from oxidation, thereby effectively improving the corrosion resistance.
[0019] Secondly, the carbon layer has a low thermal expansion coefficient, and coating it on the surface of mullite, cordierite, and corundum can effectively improve the thermal shock resistance.
[0020] Finally, the components of the inner and outer layers are basically the same except for the carbon coating modification, and the two layers have similar properties, which enables them to have good bonding and avoid the inner layer from falling off after a period of use. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] The contents of the particle size components of mullite, cordierite, corundum, leucite, carbon-coated mullite, carbon-coated cordierite, and carbon-coated corundum used in all the following embodiments and comparative examples are as follows: 5% for particles above 10 mesh; 20% for particles between 10 and 18 mesh; 15% for particles between 18 and 50 mesh; 25% for particles between 50 and 200 mesh; 25% for particles between 200 and 325 mesh; and 10% for particles below 325 mesh.
[0023] Embodiment 1:
[0024] A method for preparing a composite structure sagger for lithium battery positive electrode materials, the method for preparing a composite structure sagger for lithium battery positive electrode materials comprising the following preparation steps:
[0025] (1) Carbon coating: Mullite, cordierite and corundum were soaked in a furfuryl alcohol aqueous solution by weight, respectively, and stirred at 200 r / min for 40 min at a material-liquid ratio of 1 g / 10 ml at 80°C, and an equal volume of 0.3 mol / L oxalic acid aqueous solution was added dropwise at a rate of 3 drops per second. After the addition was completed, the mixture was stirred at 80°C and 200 r / min for 8 h, filtered, washed with pure water 3 times, vacuum dried at 50°C for 10 h, calcined at 800°C for 3 h in an argon atmosphere, with a heating rate of 5°C / min, and naturally cooled to room temperature to obtain carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum;
[0026] (2) Compression molding: Weigh 25 parts of mullite, 35 parts of cordierite, 10 parts of corundum, and 8 parts of leucite, then add 5 parts of yellow dextrin and 3 parts of water, mix evenly, age for 24 hours, put into a mold with a thickness of 12 mm, then weigh 6 parts of carbon-coated mullite, 9 parts of carbon-coated cordierite, 2.5 parts of carbon-coated corundum, 2 parts of leucite, 1 part of yellow dextrin, and 0.75 parts of water, mix evenly, age for 24 hours, and put into a mold with a thickness of 3 mm, seal and cure at room temperature for 24 hours, and press mold at a pressure of 150 MPa, hold the pressure for 10 hours, and dry at room temperature and 110° C. for 24 hours, respectively, to obtain a sagger green body;
[0027] (3) Calcination: The sagger green body is calcined at a sintering temperature and naturally cooled to room temperature to obtain a composite structure sagger for lithium battery positive electrode materials.
[0028] Embodiment 2:
[0029] A method for preparing a composite structure sagger for lithium battery positive electrode materials, the method for preparing a composite structure sagger for lithium battery positive electrode materials comprising the following preparation steps:
[0030] (1) Carbon coating: Mullite, cordierite and corundum were soaked in a furfuryl alcohol aqueous solution by weight, respectively, and stirred at 250 r / min for 35 min at a material-liquid ratio of 1 g / 10 ml at 85°C, and an equal volume of 0.3 mol / L oxalic acid aqueous solution was added dropwise at a rate of 3 drops per second. After the addition was completed, the mixture was stirred at 85°C and 250 r / min for 7 h, filtered, washed with pure water 3 times, vacuum dried at 55°C for 9 h, calcined at 850°C for 2.5 h under an argon atmosphere, with a heating rate of 5°C / min, and naturally cooled to room temperature to obtain carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum;
[0031] (2) Compression molding: Weigh 28 parts of mullite, 40 parts of cordierite, 12 parts of corundum, and 9 parts of leucite, then add 6 parts of yellow dextrin and 4 parts of water, mix evenly, age for 24 hours, put into a mold with a thickness of 13.5 mm, then weigh 6.5 parts of carbon-coated mullite, 10 parts of carbon-coated cordierite, 3 parts of carbon-coated corundum, 2.2 parts of leucite, 1.5 parts of yellow dextrin, and 1 part of water, mix evenly, age for 24 hours, and put into a mold with a thickness of 3.5 mm, seal and cure at room temperature for 24 hours, and press mold at a pressure of 150 MPa, hold the pressure for 12 hours, and dry at room temperature and 110° C. for 24 hours to obtain a sagger green body;
[0032] (3) Calcination: The sagger green body is calcined at a sintering temperature and naturally cooled to room temperature to obtain a composite structure sagger for lithium battery positive electrode materials.
[0033] Embodiment 3:
[0034] A method for preparing a composite structure sagger for lithium battery positive electrode materials, the method for preparing a composite structure sagger for lithium battery positive electrode materials comprising the following preparation steps:
[0035] (1) Carbon coating: Mullite, cordierite and corundum were soaked in a furfuryl alcohol aqueous solution by weight, stirred at 300 r / min for 30 min at a material-liquid ratio of 1 g / 10 ml at 90°C, and an equal volume of 0.3 mol / L oxalic acid aqueous solution was added dropwise at a rate of 4 drops per second. After the addition was completed, the mixture was stirred at 300 r / min for 6 h at 90°C, filtered, washed with pure water 4 times, vacuum dried at 60°C for 10 h, calcined at 900°C for 3 h under an argon atmosphere, with a heating rate of 5°C / min, and naturally cooled to room temperature to obtain carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum;
[0036] (2) Compression molding: Weigh 30 parts of mullite, 45 parts of cordierite, 15 parts of corundum, and 10 parts of leucite, then add 7 parts of yellow dextrin and 5 parts of water, mix evenly, age for 24 hours, put into a mold with a thickness of 15 mm, then weigh 7 parts of carbon-coated mullite, 11 parts of carbon-coated cordierite, 4 parts of carbon-coated corundum, 2.5 parts of leucite, 2 parts of yellow dextrin, and 1.25 parts of water, mix evenly, age for 24 hours, and put into a mold with a thickness of 4 mm, seal and cure at room temperature for 24 hours, and press mold at a pressure of 150 MPa, hold the pressure for 14 hours, and dry at room temperature and 110° C. for 24 hours to obtain a sagger green body;
[0037] (3) Calcination: The sagger green body is calcined at a sintering temperature and naturally cooled to room temperature to obtain a composite structure sagger for lithium battery positive electrode materials.
[0038] Comparative Example 1:
[0039] The preparation method of the composite structure sagger for lithium battery positive electrode material of Comparative Example 1 is different from that of Example 2 in that step (1) is not performed, and step (2) is modified as follows: pressing and molding: weigh 28 parts of mullite, 40 parts of cordierite, 12 parts of corundum, and 9 parts of leucite, add 6 parts of yellow dextrin and 4 parts of water, mix evenly, age for 24 hours, put into a mold with a thickness of 17 mm, seal and cure at room temperature for 24 hours, press and mold at a pressure of 150 MPa, maintain the pressure for 12 hours, and dry at room temperature and 110° C. for 24 hours to obtain a sagger green body. The remaining steps are the same as those of Example 2.
[0040] Comparative Example 2:
[0041] The preparation method of the composite structure sagger for lithium battery positive electrode material of Comparative Example 2 is different from that of Example 2 in that step (2) is different, and step (2) is modified as follows: pressing and molding: weighing 28 parts of mullite, 40 parts of cordierite, and 12 parts of corundum, and then adding 6 parts of yellow dextrin and 4 parts of water to mix evenly, aging for 24 hours, and first putting it into a mold according to a thickness of 13.5 mm, and then weighing 6.5 parts of carbon-coated mullite, 10 parts of carbon-coated cordierite, 3 parts of carbon-coated corundum, 1.5 parts of yellow dextrin, and 1 part of water to mix evenly, aging for 24 hours, and also putting it into a mold according to a thickness of 3.5 mm, sealing and curing at room temperature for 24 hours, pressing and molding at a pressure of 150 MPa, holding the pressure for 12 hours, and drying at room temperature and 110° C. for 24 hours, respectively, to obtain a sagger green body. The remaining steps are the same as in Example 2.
[0042] Test Example 1:
[0043] Mechanical properties test: The room temperature flexural strength, room temperature compressive strength and high temperature flexural strength are tested to evaluate the mechanical properties of the prepared composite structure sagger for lithium battery positive electrode materials. The room temperature flexural strength is tested with reference to GB / T 3001-2017, the room temperature compressive strength is tested with reference to GB / T 5072-2023, and the high temperature flexural strength is tested with reference to GB / T 5072-2023. The temperature is 1100°C and the time is 30min. Five specimens are tested in each group, and the average value data is recorded. The results are shown in Table 1.
[0044] Table 1 Mechanical properties test results
[0045] Room temperature flexural strength / MPa Normal temperature compressive strength / MPa High temperature flexural strength / MPa Example 1 23.24 86.35 18.48 Example 2 24.56 87.51 18.69 Example 3 23.87 85.93 18.21 Comparative Example 1 18.64 75.34 13.45 Comparative Example 2 15.32 59.26 11.27
[0046] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 1, it can be found that the composite structure sagger for lithium battery positive electrode material prepared in the present invention has good mechanical properties.
[0047] By comparing the data in the table, carbon coating of mullite, cordierite and corundum improves the mechanical properties and enhances durability. The addition of leucite also improves the flexural strength and compressive strength.
[0048] Test Example 2:
[0049] Thermal shock resistance test: thermal shock resistance test was carried out in accordance with GB / T 30873-2014, using the water cooling method. After 5 thermal cycles, the room temperature flexural strength was tested, and the strength retention rate was calculated and recorded. Five samples were tested in each group and the average value was recorded. The results are shown in Table 2.
[0050] Table 2 Thermal shock resistance test results
[0051] Strength retention Strength retention Example 1 79.6% Comparative Example 1 72.3% Example 2 80.7% Comparative Example 2 68.5% Example 3 79.4%
[0052] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 2, it can be found that the composite structure sagger for lithium battery positive electrode material prepared in the present invention has good thermal shock resistance.
[0053] By comparing the data in the table, it can be seen that carbon coating modification and the addition of white garnet both improve the thermal shock resistance of the composite structure sagger used for lithium battery positive electrode materials.
[0054] Test Example 3:
[0055] Corrosion resistance test: Mix the Li(Ni 0.5 Co 0.2 Mn 0.3)O2 ternary positive electrode material precursor is placed on the prepared composite structure sagger for lithium battery positive electrode material, and the average mass of the precursor material on each sample is 3g. The sample is placed in a muffle furnace, kept at 1000℃ for 4h, and taken out after natural cooling. The other samples continue to repeat the above loading, sintering, cooling and sampling operations. When the sagger sample shows serious peeling and cracking, the corrosion resistance test is terminated, and the number of repeated uses is recorded. The average value of 5 samples in each group is recorded, and the results are rounded down. The results are shown in Table 3.
[0056] Table 3 Corrosion resistance test results
[0057] Number of times of reuse Number of times of reuse Example 1 58 Comparative Example 1 38 Example 2 60 Comparative Example 2 23 Example 3 57
[0058] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the composite structure sagger for lithium battery positive electrode material prepared in the present invention has excellent corrosion resistance.
[0059] By comparing the data in the table, carbon coating modification effectively improves the corrosion resistance. The addition of white garnet not only improves the corrosion resistance but also protects the carbon layer and prolongs the service life.
[0060] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A composite structure sagger for lithium battery positive electrode material, characterized in that: The composite structure sagger for lithium battery positive electrode material is prepared by firstly impregnating mullite, cordierite and corundum in a furfuryl alcohol aqueous solution respectively, adding oxalic acid for polymerization and then calcining at high temperature to obtain carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum; mixing mullite, cordierite, corundum, leucite, yellow dextrin and water as the outer layer of the sagger, mixing carbon-coated mullite, carbon-coated cordierite, carbon-coated corundum, leucite, yellow dextrin and water as the inner layer of the sagger, and calcining the inner and outer layer structures after composite pressing and molding to obtain the composite structure sagger for lithium battery positive electrode material.
2. The composite structure sagger for lithium battery positive electrode material according to claim 1, characterized in that: The outer layer of the sagger comprises the following components by mass: 25 to 30 parts of mullite, 35 to 45 parts of cordierite, 10 to 15 parts of corundum, and 8 to 10 parts of leucite.
3. The composite structure sagger for lithium battery positive electrode material according to claim 1, characterized in that: The inner layer of the sagger comprises the following components by mass: 25 to 30 parts of carbon-coated mullite, 35 to 45 parts of carbon-coated cordierite, 10 to 15 parts of carbon-coated corundum, and 8 to 10 parts of leucite.
4. The composite structure sagger for lithium battery positive electrode material according to claim 1, characterized in that: The contents of the various particle size components of the mullite, cordierite, corundum, leucite, carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum are as follows: 3-5% for particles above 10 mesh; 20-25% for particles between 10 and 18 mesh; 15-20% for particles between 18 and 50 mesh; 20-25% for particles between 50 and 200 mesh; 20-25% for particles between 200 and 325 mesh; and 10-15% for particles below 325 mesh.
5. A method for preparing a composite structure sagger for lithium battery positive electrode material, characterized in that: The method comprises the following preparation steps: (1) Carbon coating: Mullite, cordierite and corundum were soaked in a furfuryl alcohol aqueous solution by weight, stirred at 200-300 r / min for 30-40 min at a material-liquid ratio of 1 g / 10 ml at 80-90° C., and an equal volume of 0.3 mol / L oxalic acid aqueous solution was added dropwise at 3-4 drops per second at 80-90° C., stirred at 200-300 r / min for 6-8 h, filtered, washed with pure water 3-4 times, vacuum dried at 50-60° C. for 8-10 h, calcined at 800-900° C. for 2-3 h in an argon atmosphere, with a heating rate of 5° C. / min, and naturally cooled to room temperature to obtain carbon-coated mullite, carbon-coated cordierite and carbon-coated corundum; (2) Compression molding: weigh 25-30 parts of mullite, 35-45 parts of cordierite, 10-15 parts of corundum, 8-10 parts of leucite, then add 5-7 parts of yellow dextrin and 3-5 parts of water, mix evenly, age for 24 hours, put into a mold with a thickness of 12-15 mm, then weigh 6-7 parts of carbon-coated mullite, 9-11 parts of carbon-coated cordierite, 2.5-4 parts of carbon-coated corundum, 2-2.5 parts of leucite, 1-2 parts of yellow dextrin, 0.75-1.25 parts of water, mix evenly, age for 24 hours, put into a mold with a thickness of 3-4 mm, seal and cure at room temperature for 24 hours, press and mold at a pressure of 150 MPa, hold the pressure for 10-14 hours, and dry at room temperature and 110° C. for 24 hours to obtain a sagger green body; (3) Calcination: The sagger green body is calcined at a sintering temperature and naturally cooled to room temperature to obtain a composite structure sagger for lithium battery positive electrode materials.
6. The method for preparing a composite structure sagger for lithium battery positive electrode material according to claim 5, characterized in that: The furfuryl alcohol aqueous solution in step (1) is prepared by uniformly mixing furfuryl alcohol and pure water in a volume ratio of 1:
40.
7. The method for preparing a composite structure sagger for lithium battery positive electrode material according to claim 5, characterized in that: The sintering temperature of step (3) is: 0-100°C, heating rate 1.25°C / min; 100-900°C, heating rate 5°C / min, keeping at 900°C for 30min; 900-1200°C, heating rate 4°C / min; 1200-1400°C, heating rate 2.5°C / min, keeping at 1400°C for 3h.
Citation Information
Patent Citations
Sagger for mullite-cordierite lithium battery cathode material and preparation method thereof
CN110282964A
Forming method of composite sagger
CN111574227A
Torpedo ladle lining smearing repair material, preparation method and use method
CN111943693A
Carbon source for refractory material and preparation method thereof
CN112094124A
Double-layer composite structure sagger for lithium battery positive electrode materials and preparation method of sagger
CN113416068A
